Association between inflammatory cytokines in the aqueous humor and hyperreflective foci on optical coherence tomography in patients with neovascular age-related macular degeneration and polypoidal choroidal vasculopathy - Mao, Jianbo; Chen, Nuo; Zhang, Shian; Fang, Yuyan; Zheng, Zicheng; Wu, Sulan; Ye, Xin; Chen, Yijing; Chen, Yiqi; Shen, Lijun (Frontiers in Medicine, 2022)
Purpose: To investigate the associations between cytokine levels in the aqueous humor (AH) and hyperreflective foci (HF) on spectral-domain optical coherence tomography (SD-OCT) in neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV). Methods: The retrospective study included 63 eyes with nAMD, 44 with PCV, and 43 with cataracts (Controls). AH samples were obtained before anti-vascular endothelial growth factor (VEGF) therapy or cataract surgery. Cytokines interleukin 6 (IL-6), IL-8, IL-10, interferon-inducible protein 10 (IP-10), monocyte chemotactic protein 1 (MCP-1), and VEGF were measured by multiplex bead assay. Best-corrected visual acuity (BCVA), central macular thickness (CMT), and the number of HF were evaluated at baseline and 1 month after anti-VEGF treatment. Results: No significant difference in IL-6 and IL-8 levels were noted among the three groups(P=0.370 and P=0.067). VEGF, IP-10, and IL-10 levels were significantly higher in nAMD and PCV groups than in Controls(all P<0.05). In nAMD, HF was positively correlated with VEGF (=0.300, P=0.025) and in eyes with HF group, VEGF and IL-10 were significantly higher than those without HF (P=0.008 and P=0.022). In PCV, no correlation was observed between HF and cytokines (all P>0.05). After anti-VEGF treatment, patients with HF were predisposed to worse visual outcomes (P=0.022 and P=0.015) and a significantly greater reduction in CMT (P=0.001 and P=0.057). And nAMD patients with HF were more sensitive to anti-VEGF treatment than those without HF (P=0.029). Conclusions: In the nAMD group, HF was positively correlated with VEGF. Patients in nAMD with HF had elevated levels of VEGF and IL-10 and responded favorably to anti-VEGF. HF might serve as an inflammatory biomarker and a predictive factor for therapeutic efficacy in patients with nAMD.